Fibrin monomers and association with significant hemorrhage or mortality in severely injured trauma patients. Issue 11 (November 2020) - Esnault, Pierre; Mathais, Quentin; Gueguen, Stéphanie; Cotte, Jean; Montcriol, Ambroise; Cardinale, Michaël; Goutorbe, Philippe; Bordes, Julien; Meaudre, Eric
Highlights: Post traumatic is still a leading cause of death in patients severely injured. Fibrin monomers (FMs) are a direct marker of thrombin action, and reflect coagulation activation. FMs had a poor accuracy to predict the occurrence of significant hemorrhage. However, the excellent sensitivity and NPV of FMs could help to identify patients with a low risk of bleeding during hospital care. In addition, FM levels ≥ 109.5 µg/ml might be associated with the 28-day mortality. Abstract: Background: Post-traumatic hemorrhage is still the leading cause of potentially preventable death in patients with severe trauma. Traumatic-induced coagulopathy has been described as a risk factor for significant hemorrhage and mortality in this population. Fibrin monomers (FMs) are a direct marker of thrombin action, and thus reflect coagulation activation. This study sought to determine the association of FMs levels at admission with significant hemorrhage and 28-day mortality after a severe trauma. Methods: We conducted a retrospective, observational study including all severe trauma patients admitted in a level-1 trauma center between January 2012 and December 2017. Patients with severe traumatic brain injury or previous anticoagulant / antiaggregant therapies were excluded. FMs measurements and standard coagulation test were taken at admission. Significant hemorrhage was defined as a hemorrhage requiring the transfusion of ≥ 4 Red Blood Cells units during the first 6 h. Multivariable analysis was applied to identify predictors of significant hemorrhage and a simple logistic regression analysis was applied to identify an association between FMs and 28-day mortality. Results: Overall, 299 patients were included. A total of 47 (16%) experienced a significant hemorrhage. The ROC curve demonstrated that FMs had a poor accuracy to predict the occurrence of significant hemorrhage with an AUC of 0.65 (0.57–0.74). The best threshold at 92.45 µg/ml had excellent sensitivity (87%) and negative predictive value (95%), but was not independently associated with significant hemorrhage (OR = 1.5; 95%CI (0.5–4.2)). The 28-day mortality rate was 5%. In simple logistic regression analysis, FMs values ≥109.5 µg/ml were significantly associated with 28-day mortality (unadjusted OR = 13.2; 95%CI (1.7–102)). Conclusions: FMs levels at admission are not associated with the occurrence of a significant hemorrhage in patients with severe trauma. However, the excellent sensitivity and NPV of FMs could help to identify patients with a low risk of severe bleeding during hospital care. In addition, FMs levels ≥109.5 µg/ml might be predictive of 28-day mortality.